1--2 Corinthians - Keener, Craig S., 1960- (New Cambridge Bible commentary, 2005)
Explaining 1 & 2 Corinthians passage by passage, Craig Keener uses a variety of ancient sources to demonstrate how Paul's arguments would have made sense to his 1st century readers.